Flexural biomimetic responsive building façade using a hybrid soft robot actuator and fabric membrane - Kim, Mi jin; Kim, Baek gyeom; Koh, Je sung; Yi, Hwang (Automation in Construction, 2023)
The geometrical inflexibility of rigid-body kinetic building façades is disadvantageous in free-form architecture. To address this problem, a gearless, lightweight, and geometrically flexible daylight-adaptive shading façade module is proposed by hybridizing gripper-shaped pneumatic elastomer and shape memory alloy (SMA) actuators. The compliant inflation mechanism and thermomechanical response of the bias SMA actuation achieved flexural morphology of the stretchable fabric skin and a maximum opening area ratio of ∼20%. Design feasibility, stable mobility, and structural endurance were identified through performance simulation and material testing, followed by operation tests with full-scale prototyping. This paper presents an advanced architectural application of soft robotics technology and smart material. Our findings expand the knowledge on bio-inspired designs and construction processes in climate-responsive building.
Keywords: Adaptive responsive architecture; Building facades; Fabric membranes; Freeforms; Hybrid actuator; Kinetic facades; Rigid body; Robot actuators; Soft robot; Soft robotics; Adaptive responsive architecture; Hybrid actuator; Kinetic façade; Smart material; Soft robotics